1987
DOI: 10.1002/eji.1830170613
|View full text |Cite
|
Sign up to set email alerts
|

Activation of B lymphocytes by Epstein‐Barr virus/CR2 receptor interaction

Abstract: Epstein-Barr virus (EBV) infects and transforms human B lymphocytes. The virus receptor was shown to be identical to the complement receptor CR2. The consequences of EBV/CR2 receptor interaction on B lymphocyte activation were analyzed by infection of B cells with the transforming (B95-8) and the nontransforming (P3HR1) virus strains and with UV-inactivated B95-8 virus. Similar to mitogens and antibodies against surface IgM and CR2 receptor, transforming and nontransforming EBV induced the release of leukocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…It appears from our data and from that of others that crosslinking of gp140, the C3d/EBVR, either at the cell surface of B lymphocytes by anti-gpl40 F(ab')z fragments [41], particlebound C3d [50], OKB-7, an anti-C3d/EBVR mAb [42] and UV-irradiated EBV [51] or at the cell surface of human platelets by anti-gpl40 IgG or C3d followed by anti-C3d F(ab')2 fragments, triggers cell activation in presence of other factors as T cell factors for B lymphocytes or as fibrinogen, thrombin or PAF-acether for human platelets. These data strongly support the conclusion that expression of gp140, the…”
Section: Discussionmentioning
confidence: 57%
“…It appears from our data and from that of others that crosslinking of gp140, the C3d/EBVR, either at the cell surface of B lymphocytes by anti-gpl40 F(ab')z fragments [41], particlebound C3d [50], OKB-7, an anti-C3d/EBVR mAb [42] and UV-irradiated EBV [51] or at the cell surface of human platelets by anti-gpl40 IgG or C3d followed by anti-C3d F(ab')2 fragments, triggers cell activation in presence of other factors as T cell factors for B lymphocytes or as fibrinogen, thrombin or PAF-acether for human platelets. These data strongly support the conclusion that expression of gp140, the…”
Section: Discussionmentioning
confidence: 57%
“…The binding to CR2 of multivalent ligands, as polymeric C3d/ C3dg or EBV, but not of monomeric ligands, leads to Bcell proliferation [3][4][5]. It is unknown whether the poly meric ligands induce cellular activation through dimer ization of the receptor or ligation of multiple epitopes of single CR2 molecules.…”
Section: Introductionmentioning
confidence: 99%
“…These observations are of particular interest to the biology of EBV since several independent studies have demonstrated that binding of the virus to its receptor provides the signal for at least a limited progression of the B cell into the cell cycle [7,38,53]. Thus, EBV has not only adapted to use a cell surface glycoprotein for attachment to the B cell surface, but it may also have evolved to mimic, in part, both the structure and function of the natural ligand.…”
Section: Bindingmentioning
confidence: 99%